Student vehicle identification using near field communication technology / Nora Yanti Che Jan and Mohd Nasharuddin Muhammad - Che Jan, Nora Yanti; Muhammad, Mohd Nasharuddin (UiTM Cawangan Perlis, 2018)
The purpose of this project is to develop a mobile application using NFC technology in order to assist security officers of Unit Keselamatan in UiTM Perlis branch. The main objective of the developed mobile application is to detect fake and stolen student vehicle stickers. Prior the development of the mobile application, security officers have no specific technique in detecting fake and stolen student vehicle stickers. Actions were only taken once complaints are received from the victims. NFC as defined by VasquezBriseno, Hirata et al. (2012) is a limited range high frequency wireless communication technology that allows the transfer of data among devices at distances lower than 10cm. NFC technology is a specialized subset within the family of RFID technology. The mobile application which is designed based on Automatic Identification Data Capture (AIDC) was later evaluated by ten security officers on its usability through questionnaire. Questions from the questionnaire are designed to evaluate several aspects including compatibility, content, navigation, interface design and general feedback. The results show that the officers are happy the developed mobile application as the application offers more than identifying stolen and fake vehicle stickers.